Genetic and Genomic Tools for Cannabis sativa. (1st November 2016) - Vergara, Daniela; Baker, Halie; Clancy, Kayla; Keepers, Kyle G.; Mendieta, J. Paul; Pauli, Christopher S.; Tittes, Silas B.; White, Kristin H.; Kane, Nolan C.
ABSTRACT: The Cannabis industry is currently one of the fastest growing industries in the United States. Given the changing legal status of the plant, and the rapidly advancing research, updated information on the advancement of Cannabis genomics is needed. This versatile plant is used as medicine and for food, fiber, and bioremediation. Insights from modern, high-throughput genomic technology are revolutionizing our understanding of the plant and are providing new tools to further improve our knowledge and utilization of this unique species. This review quantifies and evaluates the currently available genomic resources for Cannabis research, including six whole-genome assemblies, two transcriptomes, and 393 other substantial genomic resources, as well as other smaller publicly available genetic and genomic resources. The open-source approaches followed by many leading scientists in the field promote collaboration and facilitate these rapid advances.